Perancangan Ulang UI/UX Dengan Figma Pada Website OKE OCE Indonesia Menggunakan Metode Design Thinking - Yahya, Ahmad; Nugroho, Atmoko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The OK OCE Indonesia website plays a crucial role in supporting the OK OCE social movement, which aims to create jobs and promote economic independence through entrepreneurship development. With the advancement of digital technology and the growing expectations and needs of users, several issues have been identified in the interface design and user experience (UI/UX) of this website. The main problems identified are low user engagement due to a less intuitive design, difficult navigation, and a layout that does not support efficient information access. This research aims to redesign the UI/UX of the OK OCE Indonesia website using the Design Thinking method. This method is applied through the stages of empathy, problem definition, ideation, prototyping, and testing, to produce a user-centered and adaptable design solution. Preliminary results from this redesign show that the new design has successfully improved the quality of the user experience, particularly in terms of ease of navigation, visual consistency, and interface appeal. Overall, these changes are expected to better support the mission of OK OCE in expanding its social impact more effectively, while also contributing to entrepreneurship development in Indonesia through more efficient and responsive digital technology.